Establishment of an in vitro co-infection model of Cryptosporidium parvum and Giardia duodenalis - Manuela Kirchner; Arwid Daugschies; Cora Delling (Parasites & Vectors)
Abstract Background The two intestinal protozoan parasites Giardia duodenalis and Cryptosporidium parvum cause infections in a wide spectrum of vertebrates and have also been shown to infect suitable hosts simultaneously. To investigate potential effects between these parasites and on host cells, a co-infection model with IPEC-J2 cells was established. Methods Optimal infection conditions and several infection doses of both parasites were tested. The effect of Giardia growth medium on IPEC-J2 cells was analyzed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction assay, while the effect of different infection doses of each parasite on host cell viability was investigated by CellTiter Blue cell viability assay. For co-infection, IPEC-J2 cells were first infected with C. parvum sporozoites, and 3.5 h later, G. duodenalis trophozoites were added. Parasite propagation during single infection and co-infection were analyzed by quantitative real-time polymerase chain reaction (qPCR) as well as immunofluorescent staining. Results The infection with C. parvum sporozoites had no significant impact on cell viability, while G. duodenalis trophozoites affected cell culture in a dose dependent manner. The amount of gene copies of C. parvum in single and co-infected cells did not differ significantly, while statistically higher amounts of G. duodenalis gene copies in co-infected cell cultures were identified. Conclusions In this study, single infections and co-infections of IPEC-J2 cells with C. parvum and G. duodenalis were established and optimized over a period of 72 h. Graphical Abstract